Alpha-tomatine induces apoptosis and inhibits nuclear factor-kappa B activation on human prostatic adenocarcinoma PC-3 cells - Lee, S.T.; Wong, P.F.; Cheah, S.C.; Mustafa, Mohd Rais (Public Library of Science, 2011)
Background: Alpha-tomatine (a-tomatine) is the major saponin in tomato (Lycopersicon esculentum). This study investigates the chemopreventive potential of a-tomatine on androgen-independent human prostatic adenocarcinoma PC-3 cells.